THE CURRENT INSTRUCTIONAL PRACTICES AND PROBLEMS OF COURSE HU 2002 ENGLISH CONVERSATION 2 FACULTY OF HUMANITIES MAHAMAKUT BUDDHIST UNIVERSITY - มหาวีโร พระมหาสมัคร (Journal of Paramita, 2023)
The objectives of this research were 1) To study Current Instructional Practices and Problems of Course HU 2002 English Conversation 2; Process of teaching and learning, Personality of the teacher, Teaching media and facilities, Measurement and Evaluation and 2) To compare Current Instructional Practices and Problems of Course HU 2002 English Conversation 2. The sampling of this research was the 27 person Course HU 2002 English Conversation 2 students. The instruments used were questionnaires of 4 sections; Process of teaching and learning, Personality of the teacher, Teaching media and facilities, Measurement and Evaluation. The statistical values were the frequency, percentage, mean and standard deviation. The finding of the research were found as following; 1) The Current Instruction Practices and Problems of HU2002 English Conversation of 4 sections was the highest level of mean 3.92 S.D. .263; Measurement and Evaluation Instruction media, Teaching techniques, and Teacher personality methods 2) was the lowest level of problem in every parts of mean 1.49 S.D. .455; Measurement and Evaluation and Teacher personality, Instruction media, Teaching techniques, methods. The results to study and compare the states and problems of English learning and teaching were that The Current Instruction Practices and Problems of HU 2002 English Conversation was the highest level of mean 3.92 was the lowest level of problem in every parts of mean 1.49